Clinical translation of salivary MicroAge for understanding the oral-systemic connection in healthy longevity - Tongjun Guo; Yixuan Chen; Yuehan Yu; Yilin Shao; Cong Wang; Xue Li; Haoyu Zhang; Chao Xu; Yoo Cheung; Feng Chen; Tiansong Xu; Xiuhua Li; et al. (Frontiers in Microbiology, 2026)
The oral-systemic connection, salivary microbiome, and healthy longevity are increasingly recognized as biologically interconnected. This review summarizes lifespan changes in the salivary microbiome, its links to age-related systemic diseases, and recent progress in salivary MicroAge modeling. It further highlights advances in data preprocessing, feature engineering, and artificial intelligence-based prediction, while emphasizing the importance of standardization, generalizability, and biological interpretability for clinical translation. Overall, salivary MicroAge may provide a noninvasive and interpretable framework for biological aging assessment and healthier aging.